The Mongol Empire between myth and reality : studies in anthropological history - Aigle, Denise. (Iran Studies, 2014)
In The Mongol Empire between Myth and Reality , Denise Aigle presents the Mongol empire as a moment of contact between political ideologies, religions, cultures and languages, and, in terms of reciprocal representations, between the Far East, the Muslim East, and the Latin West. The first part is devoted to "The memoria of the Mongols in historical and literary sources" in which she examines how the Mongol rulers were perceived by the peoples with whom they were in contact. In "Shamanism and Islam" she studies the perception of shamanism by Muslim authors and their attempts to integrate Genghis Khan and his successors into an Islamic framework. The last sections deal with geopolitical questions involving the Ilkhans, the Mamluks, and the Latin West. Genghis Khan's successors claimed the protection of "Eternal Heaven" to justify their conquests even after their Islamization.